PERAN EMPOWERING LEADERSHIP DALAM MENINGKATKAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR MELALUI EMPLOYEE ENGAGEMENT SEBAGAI VARIABEL INTERVENING - Sry Rosita; Sirjaz Zais Kamal; Shofia Amin (JWM (JURNAL WAWASAN MANAJEMEN), 2021)
This study aimed to identify the relationship between empowering leadership and organizational citizenship behavior of employees at Dinas Kesehatan Kabupaten Kerinci through employee engagement. The three variables were constructed and observed the relationship among them. This research utilized quantitative research method using data collection method in the form of a questionnaire then analyzed with Partial Least Square (PLS). The analyzing steps conducted through finding the inner model, outer model and hypothesis testing. The results showed that there were relationships among these three variables. It was found that there was a positive relationship between empowering leadership toward organizational citizenship behavior, empowering leadership toward employee engagement, organizational citizenship behavior toward employee engagement, and empowering leadership toward organizational citizenship behavior through employee engagement. Therefore, it can be concluded that empowering leadership influenced the formation of organizational citizenship behavior and employee engagement of employees at Dinas Kesehatan Kabupaten Kerinci.